Philippine regional historical research fucos on Western Visayas, 1972-1998 - Funtecha, Henry F. (1999)
The period 1972-1998 marked the advent of a significant number of published books and articles dealing with the history and culture of Western Visayas. The greatest number of these materials covered the years 1993 to 1998 and were mostly on the works are on Iloilo and Negros Occidental. Not all the history researchers in the region are from the academe. The observable trends in historical research in Western Visayas are the increasing use of Filipino and Hiligaynon in the research reports, the greater variety of topics or subjects being studied the more intensive use of a wider range of sources and of an interdisciplinary approach in analyzing history, and a move towards the established of research centers devoted to the writing of local history and culture.
Keywords: Western Visayas